BIOGENIC COMPONENTS AND ELEMENTS IN SEDIMENTS OF THE CENTRAL BALTIC AND THEIR REDISTRIBUTION - Emelyanov E.M. (My University, 2001)
The content and distribution of biogenic components (CaCO3 and SiO2am) and elements (Corg, N and P) and some metals (Fe and Mn) were investigated in the marine Holocene sediments of the Baltic Sea including the Curonian and Vistula Lagoons and the Gulf of Riga. The average contents of the studied components and elements are increasing in the order: sand–coarse silt–fine silty mud–mud–pelitic (clayey) mud. The sand and the pelitic mud contain in average (in %): CaCO3 1.30 and 8.46; Corg 0.38 and 3.27; SiO2am 1.32 and 3.11; P 0.05 and 0.10; Fe 1.49 and 4.67; Mn 0.03 and 0.04, respectively. Maps of the areal distributions were compiled and show that areas of elevated values are located mainly in the central parts of lagoons or deep areas. Based on the sediment thickness it is proposed that strong near-bottom currents beneath the halocline level exist in the Eastern-Gotland Deep. The thin mud layer (or the absence of mud) and low sedimentation rates may suggest that non-deposition and resuspension of bulk sediments and associated nutrients occur in many peripheral and central parts of the Eastern-Gotland Deep at depths of more than 90–220 m.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен